A pre-lithiated fluoride cathode material and battery

Pre-lithiated fluoride cathode materials were prepared by magnetron sputtering, which solved the problems of conductivity and cycle stability of fluoride cathode materials, achieved uniform introduction and stable presence of lithium source, and improved the electrochemical performance and energy density of thin film batteries.

CN122267172APending Publication Date: 2026-06-23UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610348789.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-03-20
Publication Date
2026-06-23

AI Technical Summary

Technical Problem

Existing fluoride cathode materials in lithium metal batteries suffer from problems such as low electronic and ionic conductivity, severe polarization, limited rate performance and cycle stability, and severe irreversible capacity loss during the first charge and discharge process. In particular, in systems without lithium anodes or with limited lithium sources, it is difficult to meet the requirements of high energy density and long life.

Method used

Pre-lithiated fluoride cathode materials were prepared by magnetron sputtering. By uniformly distributing elemental metals and lithium fluoride nanoclusters within the thin film to form a conductive network, the uniform introduction and stable presence of the lithium source were improved, thus preparing the pre-lithiated fluoride cathode material.

Benefits of technology

It achieves uniform introduction and stable presence of lithium source, improves the initial efficiency, cycle stability and overall energy density of fluoride thin film cathode, and is suitable for high energy density thin film batteries and related energy storage devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122267172A_ABST
    Figure CN122267172A_ABST
Patent Text Reader

Abstract

This invention discloses a pre-lithiated fluoride cathode material and battery, relating to the field of lithium battery technology. The cathode material is a thin-film cathode composed of metal and lithium fluoride, the internal structure of which includes (110) Fe with a crystal plane spacing of 0.205 nm, (111) Ni with a crystal plane spacing of 0.2036 nm and (200) LiF with a crystal plane spacing of 0.2026 nm, and the nano-clusters of the above materials are uniformly distributed in the thin film; the specific preparation process is as follows: Step S1, after cleaning the surface of aluminum foil with anhydrous ethanol, the aluminum foil is placed in the chamber of a magnetron sputtering instrument, and then the LiF target and FeNi alloy target are fixed on the target holder respectively; Step S2, vacuum is drawn, argon gas is introduced, the internal pressure of the chamber is adjusted to 1 Pa, and pre-sputtering is performed on the LiF target and FeNi alloy target; Step S3, after the pre-sputtering is completed, sputtering begins, and the sputtering time is 50-60 min to produce the cathode material; compared with existing cathode materials, it has excellent charge and discharge performance and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, specifically to a pre-lithiated fluoride cathode material and a battery. Background Technology

[0002] With the rapid development of new energy technologies, the demand for energy storage devices with high energy density, long lifespan, and high safety is increasing in fields such as electric transportation, portable electronic devices, and distributed energy storage systems. Lithium metal batteries, due to their high theoretical specific capacity and high operating voltage, are considered an important development direction for next-generation high-energy-density rechargeable batteries. However, the specific capacity and energy density of traditional lithium-ion battery cathode materials are approaching their theoretical limits, making it difficult to meet the development needs of high-energy-density battery systems. Fluoride cathode materials (such as FeF3, NiF2, and CoF2) possess multi-electron transfer reaction characteristics, and their theoretical specific capacity and gravimetric energy density are significantly higher than traditional intercalated oxide cathode materials, thus showing promising application prospects in lithium metal batteries and solid-state battery systems. Especially in thin-film batteries, micro-energy storage devices, and integrated energy systems, fluoride thin-film cathodes, with their controllable thickness, high interface matching, and ease of integration, are suitable for use in microelectronic devices, wearable devices, and high-reliability power supplies. However, existing fluoride cathode materials still face several technical bottlenecks in practical applications. On the one hand, fluoride materials have low electronic and ionic conductivity, which leads to severe polarization and limited rate performance and cycle stability. On the other hand, fluoride cathodes are usually accompanied by significant irreversible capacity loss during the first charge and discharge process, especially in systems without lithium anodes or with limited lithium sources, resulting in low initial coulombic efficiency, which is difficult to meet the energy density and lifetime requirements of practical devices.

[0003] Pre-lithiation technology is considered one of the important means to solve the problem of lithium loss in the first cycle of fluoride cathodes. By introducing a lithium source into the cathode material or cathode film, irreversible lithium consumption can be compensated before battery assembly or in the early stages of operation, thereby improving the initial coulombic efficiency and overall electrochemical performance. Given the slow reaction kinetics of fluoride cathode materials, the metal atoms introduced by the pre-lithiation strategy can form a conductive network inside the film to facilitate electron conduction. Simultaneously, the introduced excess lithium source can effectively alleviate the problem of excessive volume deformation caused by the fluoride conversion reaction during charge and discharge. Existing pre-lithiation methods are mostly concentrated on powder cathode material systems, such as chemical pre-lithiation, physical contact pre-lithiation, or electrochemical pre-lithiation. However, these methods suffer from problems such as uneven lithium distribution, poor interface stability, complex processes, or insufficient repeatability in thin-film cathode systems, making it difficult to meet the requirements of thin-film batteries for structural integrity and process compatibility.

[0004] Therefore, there is an urgent need for a pre-lithiation technology solution suitable for fluoride thin film cathodes to achieve uniform introduction and stable presence of lithium source, improve the initial efficiency, cycle stability and overall energy density of fluoride thin film cathodes in different application scenarios and operating environments, thereby expanding their practical application in high energy density thin film batteries and related energy storage devices. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a pre-lithiated fluoride cathode material and a battery.

[0006] The objective of this invention can be achieved through the following technical solutions: A pre-lithiated fluoride cathode material is a thin film cathode composed of a metal element and lithium fluoride. The initial structure inside the thin film includes Fe with a (110) interplanar spacing of 0.205 nm, Ni with a (111) interplanar spacing of 0.2036 nm, and LiF with a (200) interplanar spacing of 0.2026 nm, and the nanoclusters of the above materials are uniformly distributed in the thin film. Specifically, the positive electrode material is made through the following steps: Step S1: After cleaning the surface of the aluminum foil with anhydrous ethanol, place the aluminum foil on the sample holder in the chamber of the magnetron sputtering instrument, and then fix the LiF target and FeNi alloy target on the two target holders respectively. Step S2: Close the chamber cover of the magnetron sputtering instrument, evacuate, and reduce the back-floor vacuum level inside the chamber to 8 × 10⁻⁶. -4 Below Pa, nitrogen gas is introduced, and the internal pressure of the chamber is adjusted to 1 Pa. The LiF target and the FeNi alloy target are pre-sputtered using radio frequency magnetron power supply and DC magnetron power supply, respectively. The pre-sputtering time is 15-25 min. Step S3: After pre-sputtering is completed, maintain the pressure constant, adjust the substrate temperature to 180-200℃, open the baffle and the rotating device, control the rotation speed to 3-5 rpm, start sputtering, and the sputtering time is 50-60 min to prepare the pre-converted lithium fluoride cathode material.

[0007] Furthermore, in step S1, the aluminum foil thickness is 20 μm, the LiF target diameter is 60 mm, the Fe and Ni atomic ratio in the FeNi alloy target is 1:1, and the FeNi alloy target diameter is 60 mm.

[0008] Furthermore, in step S3, the sputtering powers of the LiF target and the FeNi alloy target are 4.6-4.95 W / cm², respectively. -2 and 0.88-1.08 Wcm -2 .

[0009] Furthermore, the atomic ratio of F:Fe:Ni in the pre-treated lithium fluoride cathode material is 5:2:3.

[0010] A battery comprising the pre-lithiated fluoride positive electrode material prepared above, a negative electrode, and an electrolyte.

[0011] Furthermore, the negative electrode is a lithium foil.

[0012] Further, the electrolyte is prepared by the following steps: 1M LiTFSI is added to a mixed solvent consisting of 1,2-dimethoxyethane and 1,3-dioxolane, and LiNO3 is added to obtain the electrolyte, with the volume ratio of 1,2-dimethoxyethane and 1,3-dioxolane controlled at 1:1 and the mass fraction of LiNO3 at 1%.

[0013] The beneficial effects of the present invention are as follows: When the thickness of the pre-lithiated fluoride cathode material prepared by the present invention is 150 nm, the cathode material has excellent charge-discharge performance and cycle stability under the evaluation conditions of liquid half-cell, indicating that the pre-lithiated fluoride cathode material prepared by magnetron sputtering has excellent electrochemical performance. Attached Figure Description

[0014] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0015] Figure 1 These are SEM images of the surface and cross-section of the pre-lithiated fluoride cathode material of this invention; Figure 2 The charging and discharging curves during the activation process of Embodiment 1, Comparative Example 1, and Comparative Example 2 of the present invention are shown. Figure 3 This is a comparison chart of long-cycle tests for Embodiment 1, Comparative Example 1, and Comparative Example 2 of the present invention; Figure 4 This is the TEM detection result of Embodiment 1 of the present invention. Detailed Implementation

[0016] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0017] Example 1, please refer to Figure 1 As shown, a pre-lithiated fluoride cathode material is prepared through the following steps: Step S1: After cleaning the surface of the aluminum foil with anhydrous ethanol, place the aluminum foil on the sample holder in the chamber of the magnetron sputtering instrument, and then fix the LiF target and FeNi alloy target on the two target holders respectively. Step S2: Close the chamber cover of the magnetron sputtering instrument, evacuate, and reduce the back-floor vacuum level inside the chamber to 8 × 10⁻⁶. -4 Below Pa, nitrogen gas was introduced, and the internal pressure of the chamber was adjusted to 1 Pa. The LiF target and the FeNi alloy target were pre-sputtered using an RF magnetron power supply and a DC magnetron power supply, respectively, for a pre-sputtering time of 15 min. Step S3: After pre-sputtering is completed, maintain the pressure constant, adjust the substrate temperature to 180℃, open the baffle and the rotating device, control the rotation speed to 3 rpm, start sputtering, and the sputtering time is 50 min to prepare the pre-converted lithium fluoride cathode material.

[0018] In step S1, the aluminum foil thickness is 20 μm, the LiF target diameter is 60 mm, the FeNi alloy target has an Fe to Ni atomic ratio of 1:1, and the FeNi alloy target diameter is 60 mm.

[0019] In step S3, the sputtering powers of the LiF target and the FeNi alloy target are 4.6 W / cm², respectively. -2 and 0.88Wcm -2 .

[0020] Furthermore, the atomic ratio of F:Fe:Ni in the pre-treated lithium fluoride cathode material is 5:2:3.

[0021] A battery comprising the pre-lithiated fluoride positive electrode material prepared above, a negative electrode, and an electrolyte.

[0022] The negative electrode is a lithium foil.

[0023] The electrolyte is prepared by the following steps: 1M LiTFSI is added to a mixed solvent consisting of 1,2-dimethoxyethane and 1,3-dioxolane, and LiNO3 is added to obtain the electrolyte. The volume ratio of 1,2-dimethoxyethane to 1,3-dioxolane is controlled to be 1:1, and the mass fraction of LiNO3 is 1%.

[0024] Example 2: A pre-lithiated fluoride cathode material is prepared by the following steps: Step S1: After cleaning the surface of the aluminum foil with anhydrous ethanol, place the aluminum foil on the sample holder in the chamber of the magnetron sputtering instrument, and then fix the LiF target and FeNi alloy target on the two target holders respectively. Step S2: Close the chamber cover of the magnetron sputtering instrument, evacuate, and reduce the back-floor vacuum level inside the chamber to 8 × 10⁻⁶. -4Below Pa, nitrogen gas was introduced, and the internal pressure of the chamber was adjusted to 1 Pa. The LiF target and the FeNi alloy target were pre-sputtered using an RF magnetron power supply and a DC magnetron power supply, respectively. The pre-sputtering time was 20 min. Step S3: After pre-sputtering is completed, maintain the pressure constant, adjust the substrate temperature to 190℃, open the baffle and the rotating device, control the rotation speed to 4 rpm, start sputtering, and the sputtering time is 55 min to prepare the pre-treated lithium fluoride cathode material.

[0025] In step S1, the aluminum foil thickness is 20 μm, the LiF target diameter is 60 mm, the FeNi alloy target has an Fe to Ni atomic ratio of 1:1, and the FeNi alloy target diameter is 60 mm.

[0026] In step S3, the sputtering powers of the LiF target and the FeNi alloy target are 4.95 W / cm², respectively. -2 and 0.88Wcm -2 .

[0027] Furthermore, the atomic ratio of F:Fe:Ni in the pre-treated lithium fluoride cathode material is 5:2:3.

[0028] A battery comprising the pre-lithiated fluoride positive electrode material prepared above, a negative electrode, and an electrolyte.

[0029] The negative electrode is a lithium foil.

[0030] The electrolyte is prepared by the following steps: 1M LiTFSI is added to a mixed solvent consisting of 1,2-dimethoxyethane and 1,3-dioxolane, and LiNO3 is added to obtain the electrolyte. The volume ratio of 1,2-dimethoxyethane to 1,3-dioxolane is controlled to be 1:1, and the mass fraction of LiNO3 is 1%.

[0031] Example 3: A pre-lithiated fluoride cathode material is prepared by the following steps: Step S1: After cleaning the surface of the aluminum foil with anhydrous ethanol, place the aluminum foil on the sample holder in the chamber of the magnetron sputtering instrument, and then fix the LiF target and FeNi alloy target on the two target holders respectively. Step S2: Close the chamber cover of the magnetron sputtering instrument, evacuate, and reduce the back-floor vacuum level inside the chamber to 8 × 10⁻⁶. -4 Below Pa, nitrogen gas was introduced, and the internal pressure of the chamber was adjusted to 1 Pa. The LiF target and the FeNi alloy target were pre-sputtered using an RF magnetron power supply and a DC magnetron power supply, respectively. The pre-sputtering time was 25 min. Step S3: After pre-sputtering is completed, maintain the pressure, adjust the substrate temperature to 200℃, open the baffle and the rotating device, control the rotation speed to 5 rpm, start sputtering, and the sputtering time is 60 min to prepare the pre-converted lithium fluoride cathode material.

[0032] In step S1, the aluminum foil thickness is 20 μm, the LiF target diameter is 60 mm, the FeNi alloy target has an Fe to Ni atomic ratio of 1:1, and the FeNi alloy target diameter is 60 mm.

[0033] In step S3, the sputtering powers of the LiF target and the FeNi alloy target are 4.6 W / cm², respectively. -2 and 1.08Wcm -2 .

[0034] Furthermore, the atomic ratio of F:Fe:Ni in the pre-treated lithium fluoride cathode material is 5:2:3.

[0035] A battery comprising the pre-lithiated fluoride positive electrode material prepared above, a negative electrode, and an electrolyte.

[0036] The negative electrode is a lithium foil.

[0037] The electrolyte is prepared by the following steps: 1M LiTFSI is added to a mixed solvent consisting of 1,2-dimethoxyethane and 1,3-dioxolane, and LiNO3 is added to obtain the electrolyte. The volume ratio of 1,2-dimethoxyethane to 1,3-dioxolane is controlled to be 1:1, and the mass fraction of LiNO3 is 1%.

[0038] The positive electrode material foils prepared in Examples 1-3 were cut into small circular pieces with a diameter of 12 mm and assembled into CR2032 button cells in an argon-filled glove box. The optimal sputtering power parameters (0.1C, 1 C = 17.7 μA cm⁻¹) were analyzed by performing electrochemical performance tests on the cells. -2 The areal capacity results of three-cycle activation with small current are shown in Table 1.

[0039] Table 1. Aspect Ratio of Activated Three-Ring [0.1 C first cycle charge capacity (pAh / cm 2 ])]] <![CDATA[Initial discharge capacity of the first cycle (μAh / cm 2 ).]]> <![CDATA[0.1 C Third - turn charging capacity (μAh / cm 2 ).]]> <![CDATA[0.1 C Third - turn discharge capacity (μAh / cm 2 )]]> Example 1 19.91 17.35 17.79 16.9 Example 2 21.33 12.48 12.9 12.43 Example 3 18.85 11.6 12.48 11.24 As can be seen from Table 1 above, the batteries prepared in Examples 1-3 of the present invention have excellent electrochemical performance.

[0040] Please see Figures 2-3 As shown in Comparative Example 1, compared with Example 1, only the FeNi alloy target was replaced with a pure Fe target, while the other steps remained unchanged.

[0041] Comparative Example 2: Compared with Example 1, this comparative example only changed the FeNi alloy target to a pure Ni target, while the other steps remained the same.

[0042] The batteries prepared in Example 1, Comparative Example 1, and Comparative Example 2 were subjected to electrochemical performance testing using a Land CT 2001 A system. The charge-discharge curves during the 0.1 C activation process are shown below. Figure 2 As shown.

[0043] from Figure 2 It can be seen from the present invention that the pre-lithiated fluoride film cathode prepared by bimetallic elements has significant advantages over the pre-lithiated fluoride film cathode prepared by single metal elements in terms of first-cycle coulombic efficiency, areal capacity and operating voltage.

[0044] The results of long-cycle testing of the batteries prepared in Example 1, Comparative Example 1, and Comparative Example 2 are shown in the figure. Figure 3 The results show that the Fe+Ni+LiF thin film cathode has significant advantages over the Fe+LiF and Ni+LiF single metal thin film cathodes in terms of both on-plane capacity and capacity retention.

[0045] Based on the above results of the electrical performance testing of the cathode material, the cathode material prepared in Example 1 was taken and its thin film structure was subjected to TEM detection, specifically as follows: Figure 4 As shown; according to Figure 4 a. High-resolution transmission electron microscopy (HRTEM) images show that the nanodomains contain LiF, Ni and Fe, specifically (110) Fe with a spacing of 0.205 nm, (111) Ni with a spacing of 0.2036 nm, and (200) LiF with a spacing of 0.2026 nm. The three-phase nanoclusters exhibit a closely contacted structure, proving that the pre-lithiation structure does indeed enable the mixing of LiF and metal elements at the nanoscale, which will greatly reduce the electron and ion transport paths of the thin film cathode during charging and discharging.

[0046] according to Figure 4 b. Selected area electron diffraction (SAED) images show that the thin-film cathode is a polycrystalline structure composed of LiF, Ni, and Fe, consistent with the designed pre-lithiated fluoride structure.

[0047] according to Figure 4 c. EDS surface scan results show that F, Fe and Ni are uniformly distributed, and no element agglomeration occurs.

[0048] The above description is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims, they should all fall within the protection scope of the present invention.

Claims

1. A pre-lithiated fluoride cathode material, characterized in that, The internal structure of the cathode material thin film includes (110) Fe with a crystal plane spacing of 0.205 nm, (111) Ni with a crystal plane spacing of 0.2036 nm, and (200) LiF with a crystal plane spacing of 0.2026 nm. The nanoclusters of the above materials are uniformly distributed in the thin film. The positive electrode material is prepared through the following steps: Step S1: After cleaning the surface of the aluminum foil with anhydrous ethanol, place the aluminum foil in the chamber of the magnetron sputtering instrument, and then fix the LiF target and FeNi alloy target on the target holder respectively. Step S2: Close the chamber cover of the magnetron sputtering instrument, evacuate, introduce argon gas, adjust the internal pressure of the chamber to 1 Pa, and pre-sputter the LiF target and FeNi alloy target using radio frequency magnetron power supply and DC magnetron power supply respectively. Step S3: After pre-sputtering is completed, maintain the pressure constant, adjust the substrate temperature to 180-200℃, open the baffle and the rotating device, control the rotation speed to 3-5 rpm, start sputtering, and the sputtering time is 50-60 min to prepare the pre-converted lithium fluoride cathode material.

2. The pre-lithiated fluoride cathode material according to claim 1, characterized in that, During the vacuuming process in step S2, the vacuum level inside the chamber is evacuated to 8 × 10⁻⁶. -4 Below Pa.

3. The pre-lithiated fluoride cathode material according to claim 1, characterized in that, The pre-sputtering time in step S2 is 15-25 minutes.

4. The pre-lithiated fluoride cathode material according to claim 1, characterized in that, In step S1, the aluminum foil thickness is 20 μm, the LiF target diameter is 60 mm, the FeNi alloy target has an Fe to Ni atomic ratio of 1:1, and the FeNi alloy target diameter is 60 mm.

5. The pre-lithiated fluoride cathode material according to claim 1, characterized in that, In step S3, the sputtering powers of the LiF target and the FeNi alloy target are 4.6-4.95 W / cm², respectively. -2 and 0.88-1.08 Wcm -2 .

6. The pre-lithiated fluoride cathode material according to claim 1, characterized in that, The atomic ratio of F:Fe:Ni in the pre-treated lithium fluoride cathode material is 5:2:

3.

7. A battery, characterized in that, It includes the pre-lithiated fluoride cathode material, anode, and electrolyte prepared according to claim 1.

8. A battery based on a pre-lithiated fluoride cathode material according to claim 7, characterized in that, The negative electrode is a lithium foil.

9. A battery based on a pre-lithiated fluoride cathode material according to claim 7, characterized in that, The electrolyte is prepared by the following steps: 1M LiTFSI is added to a mixed solvent consisting of 1,2-dimethoxyethane and 1,3-dioxolane, and LiNO3 is added to obtain the electrolyte. The volume ratio of 1,2-dimethoxyethane to 1,3-dioxolane is controlled to be 1:1, and the mass fraction of LiNO3 is 1%.